PENGARUH UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Wilhelmus Wagener Kaleka (Bajang Institute, 2022)
This study aims to determine the effect of company size on firm value with good corporate governance as a moderation variable. This study used the population of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sampling uses the purposive sampling method, which is sampling with certain considerations and based on the interests and objectives of the study. This study used multiple linear regression analysis. The results of this study found that the company size has a positive effect on firm value. Good corporate governance as a moderation variable is able to strengthen the positive influence of the companysize on the value of the company